Contemporary Trends in Marketing Problems, Processes and Prospects - Saini, Aarti; Paul, Justin; Parayitam, Satyanarayana (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This edited volume explores marketing in the Post-COVID world and the significant changes that have recently hit the markets. It examines the newly emerging paradigms due to shifts in consumer behaviour and market responses arising from the COVID-19 crisis. The global pandemic has brought a paradigmatic change in consumer behaviour and unravelled several resilient strategies formulated and implemented by organizations to restore normalcy. This book focuses on long-term goals and survival strategies, which can be co-created with customers. Organized into seven themes, this volume will critique and connect the meaning of the "new normal" in marketing and topics such as the future of markets, post-pandemic consumer behaviour, and new marketing strategies. Aarti Saini is Associate Professor in the Department of Commerce at Shaheed Bhagat Singh College at the University of Delhi, India. Justin Paul is Full Professor in the Ph.D. & MBA programs at the University of Puerto Rico, USA and serves as Editor-in-Chief of the International Journal of Consumer Studies. Satyanarayana Parayitam is Professor of Strategic Management in the Charlton College of Business at the University of Massachusetts Dartmouth, USA.
1. Introduction Contemporary trends in Marketing: Problems Processes and Prospects -- 2. Learning to Navigate a Changing Marketing Landscape -- 3. Future of Marketing After Disruptions and Uncertainties: Physical, Digital, or Phygital? -- 4. The Digital Drivers of Consumer Behavior: Industry 4.0, Web 3.0, and Artificial Intelligence -- 5. Rethinking nation branding in the post-pandemic, post-truth era -- 6. Intelligent Automation, Service Robots, and AI - The Service Revolution Is in Full Swing -- 7. Delivering Value Through Sustainable Marketing -- 8. #BoycottLaalSinghChaddha: Failure to Leverage Twitter.
Keywords: Marketing; Consumer behavior; Technological innovations; Marketing; Consumer Behavior .; Innovation and Technology Management